PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DENGAN KEJADIAN KECELAKAAN KERJA DI TREAT AND SHIP OPERATIONS–FACILITY OPERATIONS PT CHEVRON PACIFIC INDONESIA DURI - Sri Novianti; Halinda Sari Lubis; Lina Tarigan (Lingkungan dan Kesehatan Kerja, 2014)
Implementation of Occupational Health and Safety Management Systems and Work Accident in Treat and Ship Operations-Facility Operations of PT Chevron Pacific Indonesia Duri. Occupational Health and Safety Management System gives an important role in reducing the incidence of occupational accidents and prevent health problems because of work, especially in high temperature machines and chemicals in some stages of production. Implementation of Occupational Health and Safety Management System is to minimize and even eliminate accidents. This research uses descriptive research with quantitative approach which aims to describe the implementation of the Occupational Health and Safety Management System with the accident in Treat and Ship Operations. Sample size in this study is 60 people were taken using simple random sampling technique at the Treat and Ship Operations . Data were collected by direct observation and interviews with workers using a questionnaire containing questions about implementation of Occupational Health and Safety Programmes such as Fundamental Safe Work Practice, Behaviour Based Safety, Hazard Identification, Stop Work Authority and Self Stop Work Authority. The results showed that the application of the Occupational Health and Safety Management System at the Treat and Ship Operations - Facility Operations PT Chevron Pacific Indonesia Duri included in good categories is equal to 98.3 %. Based on the research results, the PT CPI should do a direct approach to working safely and using PPE, coaching and training, particularly on Behaviour Based Safety, and also increase Occupational Health and Safety Management System in order to be better in the future. Keywords: Occupational Health and Safety Management System and, Implementation of Occupational Health and Safety Programmes, Accident,Treat and Ship Operations